Curr??culo da educa????o b??sica do Distrito Federal: um caminho para a express??o criativa do professor da escola p??blica? - Teixeira, Cristiane Leal Alves (2016)
This study investigated the ways and possibilities of development of the creative expression of teachers of fourth and fifth grade from elementary school with the implementation of the Basic Curriculum Moving the Distrito Federal Education. The research, with an emphasis on quantitative and qualitative approaches, using the mixed method, being conducted from the SEEDF documents, questionnaires, observation and semi-structured interviews. Twenty-nine teachers attended six Regional Administrative schools from Plano Piloto/Cruzeiro. The participants answered two questionnaires; three respondents were observed in teaching activities with their classes and conducted the interview. The data were submitted to the documentary analysis, descriptive statistics and content analysis. From the triangulation of data held convergent analysis of the results. The data indicated that perceptions of teachers about creativity construct refer to categories such as innovation element, the act of creating, different to the producer and troubleshooting generator. Teachers (96%) reported not having participated in training courses on creativity. On the other hand, 27,6% of respondents said they had discussed this topic in pedagogical coordination. It is inferred from the evidence that the perceptions presented by teachers on creativity come close to some descriptions reported in the literature, but are linked to common sense expressions. No intentional pedagogical actions that allow their own creative expression. Perceptions on Curriculum restricted to guiding document, everything that goes on in the classroom, to the set of objectives and contents. The results demonstrated the concern of the teacher to comply with the prescribed content for their discipline. It is noteworthy, however, that less than 50% of respondents teachers have participated in a training event on Curriculum Moving the Basic Education of the Distrito Federal. Regarding the reading of books, 15 (51,5%) participants reported having read the text on the theoretical assumptions and 22 (75,9%) Elementary School notebook Early Years. The written document, the political-pedagogical projects of schools, according to the results obtained, are not known to all teachers in schools investigated. In addition, the flexibility of the proposed content, and the development of creativity in the classroom were identified as factors dependent on the teacher's posture. The results also pointed to the need for qualitative investment in the continuing education of teachers, both in relation to the curriculum, and in relation to the creative process to be developed in the school context. Flexibility was the most highlighted feature in the analysis of the documents by setting up as an important element in building more creative teaching methods, flexible and humanized that promote development and learning effectively student.